2023
DOI: 10.1113/jp284370
|View full text |Cite
|
Sign up to set email alerts
|

Circadian regulation of glutamate release pathways shapes synaptic throughput in the brainstem nucleus of the solitary tract (NTS)

Abstract: Circadian regulation of autonomic reflex pathways pairs physiological function with the daily light cycle. The brainstem nucleus of the solitary tract (NTS) is a key candidate for rhythmic control of the autonomic nervous system. Here we investigated circadian regulation of NTS neurotransmission and synaptic throughput using patch‐clamp electrophysiology in brainstem slices from mice. We found that spontaneous quantal glutamate release onto NTS neurons showed strong circadian rhythmicity, with the highest rate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 61 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…The NTS, in turn, impacts various autonomic reflex pathways, feeding, satiety and the resulting gastrointestinal physiological responses. Importantly, all these physiological functions that are influenced by the NTS show robust circadian rhythmicity (Ragozzino et al., 2023).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The NTS, in turn, impacts various autonomic reflex pathways, feeding, satiety and the resulting gastrointestinal physiological responses. Importantly, all these physiological functions that are influenced by the NTS show robust circadian rhythmicity (Ragozzino et al., 2023).…”
mentioning
confidence: 99%
“…In the initial set of experiments, Ragozzino et al. (2023) showed that the NTS and nodose ganglia have strongly rhythmic clock gene expression. For instance, canonical gene regulatory components, such as Per1, Per2 and NR1D1 (Rev‐erbα), that underlie cellular circadian rhythmicity showed significantly diurnal expression patterns in both the NTS and the nodose ganglia (Takahashi, 2017).…”
mentioning
confidence: 99%
See 3 more Smart Citations